Identidade e intertextualidade: a construção do gênero e da sexualidade na prevenção de DST/AIDS entre travestis que se prostituem - Borba, Rodrigo (Cadernos de Linguagem e Sociedade, 2010)
This paper discusses the construction of gender and sexual identities as intertextual phenomena that emerge from local contexts of language use. More specifically, guided by a non-representational/non-essencialist perspective on language use and identity, this article investigates the discursive construction of identities in interactions drawn from safer-sex outreach work among tranvestis who work as sex professionals in an urban area in Southern Brazil. During the safer-sex outreach work interactions, Sandra and Márcia, women in gender and sex, produce non-traditional identities and bring to light interactional processes of adequation of their subject positions to the travestis’ and to the context of the interactions. Based on Wittgenstein’s (2005) and Bakhtin’s (2003; 2004) theories, I argue that the discursive production of identities is only made possible because of the intertextual aspect of social identities. Sandra and Márcia make use of intertexts that construct them as participants of the travestis’ social universe. The safer-sex outreach workers position themselves through their utterances in identity categories such as travesti, travesti’s client, and prostitute and, thus, seem to engage in sequential processes of adequation of their subject positions to their transgendered interlocutors.